Coronavirus Disease (COVID-19) Pandemic and Global Economic Circumstance (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
This research investigates the influence of the Coronavirus Disease (COVID-19) Pandemic event on the evolution of global economic circumstances, particularly among developed countries, including the United States. The research findings showed that COVID-19 has a widespread impact on inflation expectations and individuals' lifestyles and social life remarkably. These findings have consequences for actual activity, whereas careful monitoring of inflation expectations may indicate inflation anticipations un-anchoring dangers. According to these outcomes, providing a comfortable situation for finding the right job and managing life in the individual and social part by governments or any in charge organizations or workplaces is sincerely recommended. Additionally, taking care of individuals' mental health and treating suffering individuals must be considered.